2014
DOI: 10.1002/aenm.201400610
|View full text |Cite
|
Sign up to set email alerts
|

Thin HfxZr1‐xO2 Films: A New Lead‐Free System for Electrostatic Supercapacitors with Large Energy Storage Density and Robust Thermal Stability

Abstract: still smaller than that of electrochemical capacitors due mainly to the use of the low dielectric constant ( ε r ) Al 2 O 3 thin fi lm as the dielectric layer ( ε r ≈ 9). The concurrent high-power capacitors are made mainly of linear dielectric polymers with an ESD of ≈1-2 J cm −3 . [ 3 ] Although the ε r values of linear dielectric polymers are generally small (≈2-5), their electric breakdown fi elds are quite high, thereby allowing the application of high voltages, which result in a relatively high ESD. [ 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
207
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(217 citation statements)
references
References 23 publications
9
207
1
Order By: Relevance
“…Studies by Park et al even suggest a partial oxidation of the complete TiN. [41,42] Thus, the complete device stack consists of TiO x N y /TM-HfO x /FE-HfO 2 /TM-HfO x /TiO x sandwiched between two TiN electrodes, Figure 5b. Polycrystallinity of the HfO 2 layer was explicitly taken into account, creating the grain structure of the stack, as shown in Figure 5b.…”
Section: Modelingmentioning
confidence: 97%
“…Studies by Park et al even suggest a partial oxidation of the complete TiN. [41,42] Thus, the complete device stack consists of TiO x N y /TM-HfO x /FE-HfO 2 /TM-HfO x /TiO x sandwiched between two TiN electrodes, Figure 5b. Polycrystallinity of the HfO 2 layer was explicitly taken into account, creating the grain structure of the stack, as shown in Figure 5b.…”
Section: Modelingmentioning
confidence: 97%
“…The N 2 atmosphere could be regarded as an inert annealing condition, and the E int of À0. 16 During the repetitive field cycling for the wake-up process, the oxygen vacancies were believed to be redistributed in the HZO films. It is notable that the N 2 -annealed sample still contained non-negligible E int of À0.09 MV cm À1 (oxygen vacancy difference of B7.5 Â 10 11 cm À2 ) even after the full wake-up, suggesting that there was another reason that caused the non-uniform distribution of the oxygen vacancies.…”
Section: View Article Onlinementioning
confidence: 99%
“…For instance, the Pnma state in ABO 3 perovskites is known to possess antipolar motions of its A cations and recent studies found that it can also adopt the double polarization-vs.-electric field hysteresis loop in some materials 13,14 that is characteristics of antiferroelectrics 15 -therefore suggesting that Pnma states in some perovskites can hold promise towards the design of energy storage devices with high energy densities and efficiencies. [16][17][18][19][20][21][22] Interestingly, all the aforementioned works on trilinear energetic couplings have been aimed at revealing and understanding resulting static properties. In other words, the effect of these original trilinear couplings on dynamics have been left out so far and are thus basically unknown, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%